Characterization of fermented foods: bone health - Tamang, Jyoti Prakash; Agahi, Fojan; Yilmaz, Birsen; Künili, İbrahim Ender and Mardon, Julie and Bulmus-Tuccar, Tuğçe and Torbica, Aleksandra and Nikolovska Nedelkoska, Daniela and Kütt, Mary-Liis and Malagón-Rojas, Jeadran and Parada, Mayra Alejandra and Mayo, Baltasar and Frias, Juana (Frontiers in Nutrition, 2025)
Fermented foods are increasingly recognized for their potential benefits in supporting bone health, attributed to their rich content of bioactive compounds including vitamins K and B, polyphenols, peptides, and fermentation-modified phytates. This review examines how these components, enhanced in bioavailability through fermentation, may modulate bone metabolism via multiple mechanisms: improving mineral absorption, reducing inflammation, regulating oxidative stress, and influencing osteoblast and osteoclast activity. Special attention is given to the gut-bone axis, where fermented foods interact with gut microbiota to produce metabolites such as short-chain fatty acids and immunomodulatory compounds that may further support skeletal health. While preclinical and population-level studies show promising associations, clinical evidence remains limited and heterogeneous. Future research should focus on human trials, strain-specific effects, and long-term outcomes to fully establish the role of fermented foods in osteoporosis prevention and bone health maintenance.